Pelatihan Pengolahan Pakan Dan Hasil Ternak Itik Pada Kelompok Wanita Tani Ternak Desa Loyok Kecamatan Sikur Lombok Timur - Dwi Kusuma Purnamasari; Syamsuhaidi Syamsuhaidi; Sumiati Sumiati; Erwan Erwan; K.G. Wiryawan; S. Sulastri (Universitas Mataram, 2022)
Service activities aim to provide training and skills in processing duck feed and products. This activity is based on the potential of Loyok Village as a village located on the Mount Siu-Kotaraja tourism and the Tetebatu route tourist location which has been visited by many local and foreign tourists, so the village administrator hopes that Loyok Village can be more advanced to support tourism programs by having superior products of duck meat and eggs. Service activities are carried out through providing training on feed processing and making salted eggs. Salted eggs will be the flagship product of Loyok Village to be used as souvenirs for tourists. The target audience of this service activity is a group of women livestock farmers in Loyok Village. It is hoped that from this activity the community will be motivated and moved to develop livestock business so that it becomes the main livelihood and village administrators and village community leaders will support by making one of the village’s flagship programs supporting the tourism village program. The service activity was attended by the village head and his staff and 20woman farmers. Participants participated in the salted egg making training with enthusiasm, revealing the various problems faced in making salted eggs that had been carried out so far. Through this activity, participants get solutions to the problems they have faced so far. Participants are committed to producing salted eggs as souvenirs for tourists visiting and through Loyok Village